ANALYSIS OF THE APPLICATION OF THE FIXED ASSETS DEPRECIATION METHOD REVIEWED FROM THE POINT OF FINANCIAL ACCOUNTING STANDARDS (SAK) AND TAXATION - Simanjuntak, Rudyanto; Leoni Ginting (Journal of Financial Management & Accounting, 2024)
Analysis of the Application of Fixed Assets Depreciation Method from the perspective of Financial Accounting Standards (SAK) and the taxation law. The results show that the company has implemented in this case the statement of financial accounting standards No. 16 which has "converged" with International Financial Reporting Standards (IFRS) in the calculation of fixed assets. The depreciation calculation for fixed assets that is used by the company is the straight-line method. Fixed assets are calculated using the straight-line method grouped based on the classification and the rates charged are also in accordance with the tariffs imposed by the Taxation Law. The company management does not need to make fiscal corrections on the depreciation calculation of the company's fixed assets. Keywords: Depreciation, Fixed Assets, Financial Accounting Standards (SAK) Keywords: Positioning, Product Differentiation, Purchase Interest